Structural Ambiguity in the Headlines Compiled by Department of Languages, Cultures and Linguistics Bucknell University: A Study on the X-bar Theory - Elmawati, Diyah (LANTERN (Journal on English Language, Culture and Literature), 2013)
Ambiguity usually happens in the communication. Newspapers as a medium communication can also lead ambiguity to the reader, especially on the headlines. This study describes a structural ambiguity in the headlines compiled on the website of Department of Languages, Cultures and Linguistics Bucknell University. The writer used observation methods with note taking technique to collect the data. The data were then analyzed by applying X-bar theory, which principally explains that each syntactic structure has a head. The result of this study indicates that there were three causes of structural ambiguity, i.e. differences of syntactic category, placement of prepositional phrases that functions as an adjunct, and verbs subcategorization.